Pre-lithiated phosphorene material and preparation method thereof, negative electrode and lithium ion battery
By using the solution method to perform prelithiation in the negative electrode material of lithium-ion batteries, the problems of uneven lithium supplementation and high equipment requirements in the prior art are solved, and uniform prelithiation of the negative electrode and structural stability are achieved, which are suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202510127786.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-02-05
AI Technical Summary
The existing pre-lithiation technology of negative electrodes of lithium-ion batteries has problems such as uneven lithium replenishment, high equipment requirements, and the inability to improve the stability of the negative electrode at the same time.
By ultrasonicating the lithium salt and phosphorene in the first solvent, centrifugation and filtration, a prelithiated phosphorene material can be obtained. This material can be directly used to prepare the negative electrode of the lithium-ion battery, avoiding the need for special equipment, reducing the process complexity, and improving the uniformity of the prelithiation.
It realizes uniform prelithiation of the negative electrode of lithium-ion battery, improves the structural stability and cycle stability of the negative electrode, reduces the consumption of electrolyte, and is suitable for large-scale industrial production.
Smart Images

Figure CN119581554A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a pre-lithiated phosphorene material and a preparation method thereof, a negative electrode and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have become one of the most widely used electrochemical energy storage systems due to their high energy density, high operating voltage and long cycle life.
[0003] However, the conventional graphite anode used in lithium-ion batteries has a relatively low theoretical specific capacity (372 mA h g -1 ), which is difficult to meet the increasing market demand. In recent years, researchers have proposed a variety of new negative electrodes, such as phosphorene. As an emerging two-dimensional material, phosphorene has a high theoretical specific capacity (2596 mA h g -1 ) and high conductivity, it is considered to be a strong candidate for the negative electrode material of the next generation of lithium-ion batteries. However, when phosphorene is used as a negative electrode material, its poor structural stability will lead to a decrease in cycle performance, and it will also form an excessive solid electrolyte interface phase, thereby over-consuming lithium from the positive electrode.
[0004] Therefore, the pre-lithiation technology of lithium-ion battery negative electrode has become an important means to improve the performance of lithium-ion batteries. The pre-lithiation technology is to add a small amount of lithium source to the negative electrode before the formal charge and discharge cycle of the lithium-ion battery to make up for the lithium consumption in the charge and discharge reaction process of the lithium-ion battery, thereby improving the charge and discharge efficiency, energy density and cycle stability of the lithium-ion battery. The existing negative electrode pre-lithiation technologies mainly include the following: supplementing elemental lithium on the negative electrode surface, electrochemical pre-lithiation and continuous electrodeposition pre-lithiation technology. The pre-lithiation technology of supplementing elemental lithium on the negative electrode surface is to directly contact metallic lithium (such as lithium bars, lithium foil or lithium powder) with the negative electrode, and use the potential difference between the metallic lithium and the negative electrode to oxidize the metallic lithium into Li +And diffuse into the negative electrode, thereby achieving pre-lithiation. For example, Chinese invention patent CN112786971B proposes to compound metallic lithium to the surface of the negative electrode, but the pre-lithiation method faces the problem of uneven distribution of lithium ions, and involves multiple complex operations, which increases the complexity and cost of the production process. Secondly, the activity of metallic lithium is relatively high, and higher requirements are also placed on production conditions. The principle of electrochemical pre-lithiation technology is to cause an electrochemical reaction between the negative electrode and metallic lithium by applying an external voltage in the presence of an electrolyte to achieve pre-lithiation. For example, a Chinese patent application with publication number CN112542581A proposes a method for preparing a pre-lithiation agent by an electrochemical process, but special battery assembly and discharge equipment are required, the process is relatively complex, and large-scale production is difficult. The principle of continuous electrodeposition pre-lithiation technology is to achieve continuous preparation of pre-lithiation negative electrodes by continuously electrodepositing a metallic lithium layer as a lithium source. For example, Chinese invention patent CN106702441B proposes a method for preparing lithium strips with uniform thickness by continuous electrodeposition, but this method has high equipment requirements, strict process parameter control, and may also have safety issues. In addition, the above pre-lithiation technology cannot simultaneously improve the structural stability of the negative electrode.
[0005] In summary, existing negative electrode pre-lithiation technologies often have problems such as uneven lithium replenishment, high equipment requirements, and inability to simultaneously improve negative electrode stability. Summary of the invention
[0006] In order to solve the problems of uneven lithium replenishment, high equipment requirements and inability to simultaneously improve the stability of the negative electrode in the existing negative electrode pre-lithiation technology, the present invention provides a pre-lithiation phosphorene material and a preparation method thereof, a negative electrode and a lithium-ion battery.
[0007] The present invention is achieved through the following technical solutions: The invention provides a preparation method of a pre-lithiated phosphorene material, comprising: adding lithium salt and phosphorene into a first solvent, ultrasonicating, then centrifuging, filtering the obtained supernatant, and drying the obtained filter cake to obtain the pre-lithiated phosphorene material.
[0008] The present invention obtains pre-lithiated phosphorene material by directly pre-lithiating phosphorene. The pre-lithiated phosphorene material can be directly used to prepare the negative electrode of lithium-ion batteries, and there is no need to pre-lithiate the negative electrode by supplementing elemental lithium on the negative electrode surface, electrochemical pre-lithiation, or continuous electrodeposition pre-lithiation, thereby avoiding the need for special equipment and reducing the process complexity of pre-lithiation of the negative electrode. At the same time, the present invention directly pre-lithiates phosphorene, which can greatly improve the uniformity of pre-lithiation compared to other methods of pre-lithiating the negative electrode. In addition, the atoms on the surface of phosphorene can easily react with Li + The combination to form a Li-P bond can improve the structural stability of the phosphorene negative electrode, inhibit the reaction process between the phosphorus on the negative electrode surface and the electrolyte, and reduce the consumption of the electrolyte.
[0009] The method for preparing the pre-lithiated phosphorene material adopts a solution method for pre-lithiation, which can achieve uniform pre-lithiation at the atomic scale, thereby better ensuring the uniformity of the negative electrode pre-lithiation. In addition, the method of the present invention is carried out at room temperature, the reaction conditions are mild, high temperature operation is not required, the process is simple, the cost is low, the equipment requirements are low, and it is suitable for large-scale industrial production.
[0010] In the preparation method of the pre-lithiated phosphorene material of the present invention, the lithium salt is one or more of LiNO3, LiClO4, LiBF4, LiPF6, lithium borate oxalate (LiBOB), LiPO2F2, LiF, Li2CO3, CF3CO2Li and Li2O, preferably LiNO3, LiPF6 and LiPO2F2, more preferably LiNO3. The mass ratio of the lithium salt to phosphorene is (0.1-0.5):1, preferably 0.3:1.
[0011] In the preparation method of the above-mentioned pre-lithiated phosphorene material of the present invention, the first solvent is one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), ethanol, ethylene glycol, acetonitrile and acetone, preferably NMP and ethanol, and more preferably NMP.
[0012] In the method for preparing the pre-lithiated phosphorene material of the present invention, the concentration of the lithium salt in the first solvent is 0.1-3 mol L -1 , preferably 1 mol L -1 .
[0013] In the preparation method of the pre-lithiated phosphorene material of the present invention, the ultrasonic time is 0.5 to 5 h, preferably 2 h.
[0014] In some embodiments of the present invention, the method for preparing the pre-lithiated phosphorene material specifically comprises the following steps: (1) Under the protection of inert gas, add phosphorus material, grinding aid and grinding balls into the ball mill in sequence; (2) Select the ball milling method, set the ball milling speed, ball milling time and ball milling times, and perform the ball milling process under inert gas protection; (3) Under the protection of inert gas, the powder in the ball mill is taken out to obtain a few layers of phosphorene that have been exfoliated; (4) adding the phosphorene obtained in step (3) into a first solvent containing a lithium salt, performing ultrasonic exfoliation, and then centrifuging, filtering the supernatant containing the monolayer and few-layer phosphorene, and drying the filter cake obtained by filtration to obtain a pre-lithiated phosphorene material.
[0015] In the above step (1) of the present invention, the phosphorus material is preferably one or more of red phosphorus powder, black phosphorus powder and block black phosphorus. In some more preferred embodiments, the phosphorus material is block black phosphorus.
[0016] In the above step (1) of the present invention, the grinding aid is preferably one or more of graphite, silicon dioxide, carbon black, gypsum, talc, coke rosin, potassium ferrocyanide, stearic acid, ethanol, ethylene glycol, propylene glycol, diethylene glycol, methanol, glycerol, triethanolamine, diisopropanolamine, oleic acid, lignin sulfonate (e.g. sodium lignin sulfonate), polyacrylate (e.g. polymethyl methacrylate, polyethyl methacrylate), polycarboxylate (e.g. sodium polyacrylate) and stearate (e.g. calcium stearate). In some more preferred embodiments, the grinding aid is graphite, ethanol and ethylene glycol, more preferably graphite.
[0017] In the above step (1) of the present invention, the grinding balls are preferably one or more of steel balls, ceramic balls, zirconia balls and glass balls. In some more preferred embodiments, the grinding balls are steel balls and zirconia balls.
[0018] In the above step (1) of the present invention, the mass ratio of the phosphorus material to the grinding aid is preferably (85-95):1, and the mass ratio of the phosphorus material to the grinding ball is preferably (0.01-0.5):1. In some more preferred embodiments, the mass ratio of the phosphorus material to the grinding aid is 90:1, and the mass ratio of the phosphorus material to the grinding ball is 0.02:1.
[0019] In the above step (2) of the present invention, the ball milling method is one of high-energy oscillating ball milling, drum ball milling and plasma ball milling, and high-energy oscillating ball milling is preferred.
[0020] In the above step (2) of the present invention, the ball milling speed is 500-1200 rpm, the ball milling time is 0.25-1 h, and the number of ball millings is 5-40 times. In some more preferred embodiments, the ball milling speed is 900 rpm, the ball milling time is 0.5 h, and the number of ball millings is 20 times.
[0021] The present invention also provides a pre-lithiated phosphorene material prepared by the above method, wherein the pre-lithiated phosphorene material comprises phosphorene and lithium element, and the lithium element forms a Li-P bond with phosphorene.
[0022] The present invention also provides a negative electrode, which comprises a current collector and a negative electrode material loaded on the current collector, wherein the negative electrode material is the pre-lithiated phosphorene material as described above.
[0023] The method for preparing the negative electrode of the present invention comprises: mixing the pre-lithiation phosphorene material, the conductive agent and the binder, adding the mixture into a second solvent, stirring to obtain slurry; coating the slurry on a current collector, drying to obtain the negative electrode.
[0024] In the above-mentioned method for preparing the negative electrode of the present invention, the mass ratio of the pre-lithiated phosphorene material, the conductive agent and the binder is (8~9.5):(0.25~1):(0.25~1), preferably 9:0.5:0.5.
[0025] In the above-mentioned method for preparing the negative electrode of the present invention, the second solvent is one or more of NMP, DMF and ethanol, preferably NMP.
[0026] Specifically, the preparation method of the negative electrode includes: 1) After the prepared pre-lithiated phosphorene material, conductive agent and binder are stirred and mixed evenly, the mixture is added into a second solvent and stirred to prepare a slurry; 2) The slurry is coated on a current collector to form an electrode sheet, and the electrode sheet is dried to obtain a pre-lithiated negative electrode.
[0027] In the above step 1) of the present invention, a stirring deaerator is preferably used for stirring, and the stirring time is 0.25 to 2 h, for example, the stirring time is 0.5 h.
[0028] In the above step 2) of the present invention, the current collector can be made of copper foil, and the electrode sheet is preferably vacuum dried at a vacuum drying temperature of 60-120°C for 8-24 h; for example, the vacuum drying temperature is 100°C for 12 h.
[0029] Based on the prepared pre-lithiated negative electrode, the present invention also provides a lithium ion battery.
[0030] In some specific embodiments of the present invention, the lithium-ion battery is assembled as follows: in a glove box, the negative electrode prepared as above is used as the negative electrode, metallic lithium is used as the counter electrode, an electrolyte is added, and a button-type lithium-ion battery is assembled.
[0031] The electrolyte is a mixture of EC (Ethylene Carbonate) and DEC (Dimethyl Carbonate) containing 1.0 M LiPF6 and 5.0 wt.% FEC (Fluoroethylene Carbonate) (the volume ratio of EC and DEC is 1:1), or a mixture of EC, DEC and EMC (EthylMethyl Carbonate) containing 1.0 M LiPF6 (the volume ratio of EC, DEC and EMC is 1:1:1), or a mixture of EC, DEC and EMC containing 1.2 MLiPF6 (the volume ratio of EC, DEC and EMC is 1:1:1), or a mixture of EC and DEC containing 1.0 M LiPF6 (the volume ratio of EC and DEC is 1:1). Preferably, the electrolyte is a mixture of EC and DEC containing 1.0 M LiPF6 and 5.0 wt.% FEC (the volume ratio of EC and DEC is 1:1).
[0032] Compared with the prior art, the present invention has the following beneficial effects: The method for preparing the pre-lithiated phosphorene material of the present invention uses phosphorene as a raw material and a lithium salt as a lithiation agent, and reacts the phosphorene surface atoms and Li + Combined to form Li-P bonds, thereby obtaining pre-lithiated phosphorene materials. The present invention adopts a solution method to pre-lithiate phosphorene. On the one hand, uniform pre-lithiation can be achieved on an atomic scale, thereby better ensuring the uniformity of pre-lithiation of the negative electrode prepared based on the pre-lithiated phosphorene material; on the other hand, the method of the present invention has mild reaction conditions, does not require high-temperature operation, has a fast reaction speed, is simple in process, has low cost, has low equipment requirements, and is suitable for large-scale industrial production.
[0033] The pre-lithiated phosphorene material prepared by the present invention is doped with lithium element. When the pre-lithiated phosphorene material is used to prepare the negative electrode of a lithium-ion battery, the obtained negative electrode itself already contains lithium element. Therefore, there is no need to pre-lithiate the negative electrode by supplementing elemental lithium on the surface of the negative electrode, electrochemical pre-lithiation, or continuous electrodeposition pre-lithiation, thereby avoiding the need for special equipment and reducing the process complexity of pre-lithiation of the negative electrode. At the same time, the distribution of lithium element in the negative electrode prepared based on the pre-lithiated phosphorene material of the present invention is more uniform, which can greatly improve the uniformity of pre-lithiation of the negative electrode compared to other methods of pre-lithiating the negative electrode through subsequent processes. In addition, the surface atoms of phosphorene and Li + After combining to form the Li-P bond, the highly active atoms on the surface of phosphorene can be prevented from reacting with the electrolyte during the charging and discharging process, thereby achieving the purpose of improving the stability of the negative electrode structure.
[0034] The negative electrode based on the pre-lithiated phosphorene material of the present invention can be used as a pre-lithiated negative electrode by itself, and no pre-lithiation is required by technologies such as supplementing elemental lithium on the surface of the negative electrode, electrochemical pre-lithiation, or continuous electrodeposition pre-lithiation, thereby avoiding the need for special equipment. At the same time, the distribution of lithium elements in the negative electrode based on the pre-lithiated phosphorene material of the present invention is more uniform, which can improve the structural stability of the negative electrode.
[0035] The present invention assembles a lithium-ion battery based on the negative electrode of the pre-lithiated phosphorene material, and the use of the pre-lithiated phosphorene material improves the cycle stability and life of the lithium-ion battery. The lithium-ion battery can be applied to new energy vehicles, portable electronic devices, power grid energy storage, energy storage power stations and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 This is a scanning electron microscope image (SEM image) of the pre-lithiated phosphorene material prepared in Example 2 of the present invention.
[0038] Figure 2 This is an X-ray photoelectron spectroscopy (XPS) graph of the pre-lithiated phosphorene material prepared in Example 2 of the present invention.
[0039] Figure 3 Electrochemical impedance diagrams of lithium ion batteries assembled according to Example 2, Example 8, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention.
[0040] Figure 4 The cycle-specific capacity diagram of the lithium ion batteries assembled according to Example 2, Example 8, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention.
[0041] Figure 5 The cycle-efficiency diagram of the lithium-ion batteries assembled according to Example 2, Example 8, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0042] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0043] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0044] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0045] Example 1 (1) In an argon glove box, 1.8 g of bulk black phosphorus, 0.02 g of graphite, and 90 g of grinding balls were added sequentially into a high-energy oscillating ball mill.
[0046] (2) Turn on the power of the high-energy oscillating ball mill, set the ball mill speed to 900 rpm, the one-way interval running time to 30 min, the timing time to 30 min, and the restart times to 19 times. Fix the high-energy oscillating ball mill jar on the frame of the high-energy oscillating ball mill, turn on the high-energy oscillating ball mill for high-energy oscillating ball milling, and the ball milling time is 10 h.
[0047] (3) Open the high-energy oscillating ball mill in an argon glove box, take out the powder in the high-energy oscillating ball mill, and obtain the exfoliated few-layer phosphorene powder.
[0048] (4) Add 0.1 g of LiNO3 powder to a sample bottle containing 100 mL of NMP solvent and stir evenly to obtain a lithium salt solution; take 1 g of the few-layer phosphorene powder obtained above and add it to the lithium salt solution. Place the sample bottle in an ultrasonic machine for 2 h, then centrifuge, filter the supernatant, and dry the filter cake to obtain a clean product, which is the pre-lithiated phosphorene material.
[0049] (5) The pre-lithiated phosphorene material, conductive agent and binder prepared above were mixed evenly in a mass ratio of 9:0.5:0.5, and then added to NMP solvent and stirred for 0.5 h using a stirring degassing machine to prepare a slurry. The slurry was coated on copper foil to make an electrode sheet, and the electrode sheet was transferred to a vacuum drying oven and dried at 100 °C for 12 h.
[0050] (6) In a glove box, the electrode sheet prepared in step (5) was used as the negative electrode, metallic lithium was used as the counter electrode, and 2 drops of electrolyte (a mixture of EC and DEC containing 1.0 M LiPF6 and 5.0 wt.% FEC (the volume ratio of EC and DEC was 1:1)) were added to assemble a button-type lithium-ion battery for testing. The test conditions were: test temperature of 30 °C, charge and discharge current density of 0.5 A g -1 , charge and discharge cut-off voltage is 0.01-3.0 V (vs. Li / Li + ).
[0051] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in Example 1 is 1583 mA h g -1 , the capacity retention rate after 50 cycles is 82.2%.
[0052] Example 2 (1) In an argon glove box, 1.8 g of bulk black phosphorus, 0.02 g of graphite, and 90 g of grinding balls were added sequentially into a high-energy oscillating ball mill.
[0053] (2) Turn on the power of the high-energy oscillating ball mill, set the ball mill speed to 900 rpm, the one-way interval running time to 30 min, the timing time to 30 min, and the restart times to 19 times. Fix the high-energy oscillating ball mill jar on the frame of the high-energy oscillating ball mill, turn on the high-energy oscillating ball mill for high-energy oscillating ball milling, and the ball milling time is 10 h. (3) Open the high-energy oscillating ball mill in an argon glove box, take out the powder in the high-energy oscillating ball mill, and obtain the exfoliated few-layer phosphorene powder.
[0054] (4) Add 0.3 g of LiNO3 powder to a sample bottle containing 100 mL of NMP solvent and stir evenly to obtain a lithium salt solution; take 1 g of the few-layer phosphorene powder obtained above and add it to the lithium salt solution. Place the sample bottle in an ultrasonic machine for 2 h, then centrifuge, filter the supernatant, and dry the filter cake to obtain a clean product, which is the pre-lithiated phosphorene material.
[0055] (5) The pre-lithiated phosphorene material, conductive agent and binder prepared above were mixed evenly in a mass ratio of 9:0.5:0.5, and then added to NMP solvent and stirred for 0.5 h using a stirring degassing machine to prepare a slurry. The slurry was coated on copper foil to make an electrode sheet, and the electrode sheet was transferred to a vacuum drying oven and dried at 100 °C for 12 h.
[0056] (6) In a glove box, the electrode sheet prepared in step (5) was used as the negative electrode, metallic lithium was used as the counter electrode, and 2 drops of electrolyte (a mixture of EC and DEC containing 1.0 M LiPF6 and 5.0 wt.% FEC (the volume ratio of EC and DEC was 1:1)) were added to assemble a button-type lithium-ion battery for testing. The test conditions were: test temperature of 30 °C, charge and discharge current density of 0.5 A g -1 , the charge and discharge cut-off voltage is 0.01~3.0 V (vs. Li / Li + ).
[0057] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in Example 2 is 1659 mAh g -1 , the capacity retention rate after 50 cycles is 86.6%.
[0058] Example 3 (1) In an argon glove box, 1.8 g of bulk black phosphorus, 0.02 g of graphite, and 90 g of grinding balls were added sequentially into a high-energy oscillating ball mill.
[0059] (2) Turn on the power of the high-energy oscillating ball mill, set the ball mill speed to 900 rpm, the one-way interval running time to 30 min, the timing time to 30 min, and the restart times to 19 times. Fix the high-energy oscillating ball mill jar on the frame of the high-energy oscillating ball mill, turn on the high-energy oscillating ball mill for high-energy oscillating ball milling, and the ball milling time is 10 h. (3) Open the high-energy oscillating ball mill in an argon glove box, take out the powder in the high-energy oscillating ball mill, and obtain the exfoliated few-layer phosphorene powder.
[0060] (4) Add 0.4 g of LiNO3 powder to a sample bottle containing 100 mL of NMP solvent and stir evenly to obtain a lithium salt solution; take 1 g of the few-layer phosphorene powder obtained above and add it to the lithium salt solution. Place the sample bottle in an ultrasonic machine for 2 h, then centrifuge, filter the supernatant, and dry the filter cake to obtain a clean product, which is the pre-lithiated phosphorene material.
[0061] (5) The pre-lithiated phosphorene material, conductive agent and binder prepared above were mixed evenly in a mass ratio of 9:0.5:0.5, and then added to NMP solvent and stirred for 0.5 h using a stirring degassing machine to prepare a slurry. The slurry was coated on copper foil to make an electrode sheet, and the electrode sheet was transferred to a vacuum drying oven and dried at 100 °C for 12 h.
[0062] (6) In a glove box, the electrode sheet prepared in step (5) was used as the negative electrode, metallic lithium was used as the counter electrode, and 2 drops of electrolyte (a mixture of EC and DEC containing 1.0 M LiPF6 and 5.0 wt.% FEC (the volume ratio of EC and DEC was 1:1)) were added to assemble a button-type lithium-ion battery for testing. The test conditions were: test temperature of 30 °C, charge and discharge current density of 0.5 A g -1 , the charge and discharge cut-off voltage is 0.01~3.0 V (vs. Li / Li + ).
[0063] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in Example 3 is 1550 mA h g -1 , the capacity retention rate after 50 cycles is 85.4%.
[0064] Example 4 (1) In an argon glove box, 1.8 g of bulk black phosphorus, 0.02 g of graphite, and 90 g of grinding balls were added sequentially into a high-energy oscillating ball mill.
[0065] (2) Turn on the power of the high-energy oscillating ball mill, set the ball mill speed to 900 rpm, the one-way interval running time to 30 min, the timing time to 30 min, and the restart times to 19 times. Fix the high-energy oscillating ball mill jar on the frame of the high-energy oscillating ball mill, turn on the high-energy oscillating ball mill for high-energy oscillating ball milling, and the ball milling time is 10 h. (3) Open the high-energy oscillating ball mill in an argon glove box, take out the powder in the high-energy oscillating ball mill, and obtain the exfoliated few-layer phosphorene powder.
[0066] (4) Add 0.5 g of LiNO3 powder to a sample bottle containing 100 mL of NMP solvent and stir evenly to obtain a lithium salt solution; take 1 g of the few-layer phosphorene powder obtained above and add it to the lithium salt solution. Place the sample bottle in an ultrasonic machine for 2 h, then centrifuge, filter the supernatant, and dry the filter cake to obtain a clean product, which is the pre-lithiated phosphorene material.
[0067] (5) The pre-lithiated phosphorene material, conductive agent and binder prepared above were mixed evenly in a mass ratio of 9:0.5:0.5, and then added to NMP solvent and stirred for 0.5 h using a stirring degassing machine to prepare a slurry. The slurry was coated on copper foil to make an electrode sheet, and the electrode sheet was transferred to a vacuum drying oven and dried at 100 °C for 12 h.
[0068] (6) In a glove box, the electrode sheet prepared in step (5) was used as the negative electrode, metallic lithium was used as the counter electrode, and 2 drops of electrolyte (a mixture of EC and DEC containing 1.0 M LiPF6 and 5.0 wt.% FEC (the volume ratio of EC and DEC was 1:1)) were added to assemble a button-type lithium-ion battery for testing. The test conditions were: test temperature of 30 °C, charge and discharge current density of 0.5 A g -1 , the charge and discharge cut-off voltage is 0.01~3.0 V (vs. Li / Li + ).
[0069] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in Example 4 is 1575 mA h g -1 , the capacity retention rate after 50 cycles is 82.3%.
[0070] Example 5 (1) In an argon glove box, 1.8 g of bulk black phosphorus, 0.02 g of graphite, and 90 g of grinding balls were added sequentially into a high-energy oscillating ball mill.
[0071] (2) Turn on the power of the high-energy oscillating ball mill, set the ball mill speed to 900 rpm, the one-way interval running time to 30 min, the timing time to 30 min, and the restart times to 19 times. Fix the high-energy oscillating ball mill jar on the frame of the high-energy oscillating ball mill, turn on the high-energy oscillating ball mill for high-energy oscillating ball milling, and the ball milling time is 10 h.
[0072] (3) Open the high-energy oscillating ball mill in an argon glove box, take out the powder in the high-energy oscillating ball mill, and obtain the exfoliated few-layer phosphorene powder.
[0073] (4) Add 0.3 g of LiNO3 powder to a sample bottle containing 100 mL of NMP solvent and stir evenly to obtain a lithium salt solution; take 1 g of the few-layer phosphorene powder obtained above and add it to the lithium salt solution. Place the sample bottle in an ultrasonic machine for 0.5 h, then centrifuge, filter the supernatant, and dry the filter cake to obtain a clean product, which is the pre-lithiated phosphorene material.
[0074] (5) The pre-lithiated phosphorene material, conductive agent and binder prepared above were mixed evenly in a mass ratio of 9:0.5:0.5, and then added to NMP solvent and stirred for 0.5 h using a stirring degassing machine to prepare a slurry. The slurry was coated on copper foil to make an electrode sheet, and the electrode sheet was transferred to a vacuum drying oven and dried at 100 °C for 12 h.
[0075] (6) In a glove box, the electrode sheet prepared in step (5) was used as the negative electrode, metallic lithium was used as the counter electrode, and 2 drops of electrolyte (a mixture of EC and DEC containing 1.0 M LiPF6 and 5.0 wt.% FEC (the volume ratio of EC and DEC was 1:1)) were added to assemble a button-type lithium-ion battery for testing. The test conditions were: test temperature of 30 °C, charge and discharge current density of 0.5 A g -1 , the charge and discharge cut-off voltage is 0.01~3.0 V (vs. Li / Li + ).
[0076] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in Example 5 is 1580 mA h g -1 , the capacity retention rate after 50 cycles is 81.2%.
[0077] Example 6 (1) In an argon glove box, 1.8 g of bulk black phosphorus, 0.02 g of graphite, and 90 g of grinding balls were added sequentially into a high-energy oscillating ball mill.
[0078] (2) Turn on the power of the high-energy oscillating ball mill, set the ball mill speed to 900 rpm, the one-way interval running time to 30 min, the timing time to 30 min, and the restart times to 19 times. Fix the high-energy oscillating ball mill jar on the frame of the high-energy oscillating ball mill, turn on the high-energy oscillating ball mill for high-energy oscillating ball milling, and the ball milling time is 10 h. (3) Open the high-energy oscillating ball mill in an argon glove box, take out the powder in the high-energy oscillating ball mill, and obtain the exfoliated few-layer phosphorene powder.
[0079] (4) Add 0.3 g of LiNO3 powder to a sample bottle containing 100 mL of NMP solvent and stir evenly to obtain a lithium salt solution; take 1 g of the few-layer phosphorene powder obtained above and add it to the lithium salt solution. Place the sample bottle in an ultrasonic machine for 3 h, then centrifuge, filter the supernatant, and dry the filter cake to obtain a clean product, which is the pre-lithiated phosphorene material.
[0080] (5) The pre-lithiated phosphorene material, conductive agent and binder prepared above were mixed evenly in a mass ratio of 9:0.5:0.5, and then added to NMP solvent and stirred for 0.5 h using a stirring degassing machine to prepare a slurry. The slurry was coated on copper foil to make an electrode sheet, and the electrode sheet was transferred to a vacuum drying oven and dried at 100 °C for 12 h.
[0081] (6) In a glove box, the electrode sheet prepared in step (5) was used as the negative electrode, metallic lithium was used as the counter electrode, and 2 drops of electrolyte (a mixture of EC and DEC containing 1.0 M LiPF6 and 5.0 wt.% FEC (the volume ratio of EC and DEC was 1:1)) were added to assemble a button-type lithium-ion battery for testing. The test conditions were: test temperature of 30 °C, charge and discharge current density of 0.5 A g -1 , the charge and discharge cut-off voltage is 0.01~3.0 V (vs. Li / Li + ).
[0082] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in Example 6 is 1602 mAh g -1 , the capacity retention rate after 50 cycles is 83.5%.
[0083] Example 7 (1) In an argon glove box, 1.8 g of bulk black phosphorus, 0.02 g of graphite, and 90 g of grinding balls were added sequentially into a high-energy oscillating ball mill.
[0084] (2) Turn on the power of the high-energy oscillating ball mill, set the ball mill speed to 900 rpm, the one-way interval running time to 30 min, the timing time to 30 min, and the restart times to 19 times. Fix the high-energy oscillating ball mill jar on the frame of the high-energy oscillating ball mill, turn on the high-energy oscillating ball mill for high-energy oscillating ball milling, and the ball milling time is 10 h. (3) Open the high-energy oscillating ball mill in an argon glove box, take out the powder in the high-energy oscillating ball mill, and obtain the exfoliated few-layer phosphorene powder.
[0085] (4) Add 0.3 g of LiNO3 powder to a sample bottle containing 100 mL of NMP solvent and stir evenly to obtain a lithium salt solution; take 1 g of the few-layer phosphorene powder obtained above and add it to the lithium salt solution. Place the sample bottle in an ultrasonic machine for 5 h, then centrifuge it, filter the supernatant, and dry the filter cake to obtain a clean product, which is the pre-lithiated phosphorene material.
[0086] (5) The pre-lithiated phosphorene material, conductive agent and binder prepared above were mixed evenly in a mass ratio of 9:0.5:0.5, and then added to NMP solvent and stirred for 0.5 h using a stirring degassing machine to prepare a slurry. The slurry was coated on copper foil to make an electrode sheet, and the electrode sheet was transferred to a vacuum drying oven and dried at 100 °C for 12 h.
[0087] (6) In a glove box, the electrode sheet prepared in step (5) was used as the negative electrode, metallic lithium was used as the counter electrode, and 2 drops of electrolyte (a mixture of EC and DEC containing 1.0 M LiPF6 and 5.0 wt.% FEC (the volume ratio of EC and DEC was 1:1)) were added to assemble a button-type lithium-ion battery for testing. The test conditions were: test temperature of 30 °C, charge and discharge current density of 0.5 A g -1 , the charge and discharge cut-off voltage is 0.01~3.0 V (vs. Li / Li + ).
[0088] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in Example 7 is 1572 mA h g -1 , the capacity retention rate after 50 cycles is 81.5%.
[0089] Example 8 (1) In an argon glove box, 1.8 g of red phosphorus powder, 0.02 g of ethanol, and 90 g of grinding balls were added into a high-energy oscillating ball mill in sequence.
[0090] (2) Turn on the power of the high-energy oscillating ball mill, set the ball mill speed to 900 rpm, the one-way interval running time to 30 min, the timing time to 30 min, and the restart times to 19 times. Fix the high-energy oscillating ball mill jar on the frame of the high-energy oscillating ball mill, turn on the high-energy oscillating ball mill for high-energy oscillating ball milling, and the ball milling time is 10 h. (3) Open the high-energy oscillating ball mill in an argon glove box, take out the powder in the high-energy oscillating ball mill, and obtain the exfoliated few-layer phosphorene powder.
[0091] (4) Add 0.3 g of LiPF6 powder to a sample bottle containing 100 mL of NMP solvent and stir evenly to obtain a lithium salt solution; take 1 g of the few-layer phosphorene powder obtained above and add it to the lithium salt solution. Place the sample bottle in an ultrasonic machine for 2 h, then centrifuge, filter the supernatant, and dry the filter cake. The clean product obtained is the pre-lithiated phosphorene material.
[0092] (5) The pre-lithiated phosphorene material, conductive agent and binder prepared above were mixed evenly in a mass ratio of 9:0.5:0.5, and then added to NMP solvent and stirred for 0.5 h using a stirring degassing machine to prepare a slurry. The slurry was coated on copper foil to make an electrode sheet, and the electrode sheet was transferred to a vacuum drying oven and dried at 100 °C for 12 h.
[0093] (6) In a glove box, the electrode sheet prepared in step (5) was used as the negative electrode, metallic lithium was used as the counter electrode, and 2 drops of electrolyte (a mixture of EC and DEC containing 1.0 M LiPF6 and 5.0 wt.% FEC (the volume ratio of EC and DEC was 1:1)) were added to assemble a button-type lithium-ion battery for testing. The test conditions were: test temperature of 30 °C, charge and discharge current density of 0.5 A g -1 , the charge and discharge cut-off voltage is 0.01~3.0 V (vs. Li / Li + ).
[0094] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in Example 8 is 1350 mA h g -1 , the capacity retention rate after 50 cycles is 86.1%.
[0095] Example 9 (1) In an argon glove box, 1.8 g black phosphorus powder, 0.02 g ethylene glycol, and 90 g grinding balls were added into a high-energy oscillating ball mill in sequence.
[0096] (2) Turn on the power of the high-energy oscillating ball mill, set the ball mill speed to 1200 rpm, the one-way interval running time to 60 min, the timing time to 60 min, and the restart times to 5 times. Fix the high-energy oscillating ball mill jar on the frame of the high-energy oscillating ball mill, turn on the high-energy oscillating ball mill for high-energy oscillating ball milling, and the ball milling time is 5 h. (3) Open the high-energy oscillating ball mill in an argon glove box, take out the powder in the high-energy oscillating ball mill, and obtain the exfoliated few-layer phosphorene powder.
[0097] (4) Add 0.3 g of LiPO2F2 powder to a sample bottle containing 100 mL of ethanol solvent and stir well to obtain a lithium salt solution; take 1 g of the few-layer phosphorene powder obtained above and add it to the lithium salt solution. Place the sample bottle in an ultrasonic machine for 2 h, then centrifuge, filter the supernatant, and dry the filter cake. The clean product obtained is the pre-lithiated phosphorene material.
[0098] (5) The pre-lithiated phosphorene material, conductive agent and binder prepared above were mixed evenly in a mass ratio of 8:1:1, and then added to NMP solvent and stirred for 2 h using a stirring degassing machine to prepare a slurry. The slurry was coated on copper foil to make an electrode sheet, and the electrode sheet was transferred to a vacuum drying oven and dried at 120 °C for 8 h.
[0099] (6) In a glove box, the electrode sheet prepared in step (5) was used as the negative electrode, metallic lithium was used as the counter electrode, and 2 drops of electrolyte (a mixture of EC and DEC containing 1.0 M LiPF6 and 5.0 wt.% FEC (the volume ratio of EC and DEC was 1:1)) were added to assemble a button-type lithium-ion battery for testing. The test conditions were: test temperature of 30 °C, charge and discharge current density of 0.5 A g -1 , the charge and discharge cut-off voltage is 0.01~3.0 V (vs. Li / Li + ).
[0100] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in Example 9 is 1450 mA h g -1 , the capacity retention rate after 50 cycles is 82.2%.
[0101] Comparative Example 1 This comparative example is a phosphorene material that has not been pre-lithiated. The preparation method and performance test of the phosphorene material are basically the same as those in Example 2, except that LiNO3 powder is not added to the NMP solvent in step (4), that is, phosphorene is not pre-lithiated.
[0102] The first reversible specific capacity of the phosphorene material prepared in this comparative example 1 is 1010 mAh g -1 , the capacity retention rate after 50 cycles is 80.6%.
[0103] Comparative Example 2 In this comparative example, metal lithium foil was used to pre-lithiate the phosphorene material. The preparation method and performance test of the phosphorene material were basically the same as those in Example 2, except that the pre-lithiation process in step (4) was as follows: 1 g of few-layer phosphorene powder and 0.3 g of lithium foil were added to a crucible in a glove box and calcined at 350 °C for 2 h to obtain the pre-lithiated phosphorene material.
[0104] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in this comparative example 2 is 1251 mA h g -1 , the capacity retention rate after 50 cycles is 78.3%.
[0105] Comparative Example 3 In this comparative example, metal lithium powder was used to pre-lithiate the phosphorene material. The preparation method and performance test of the phosphorene material were basically the same as those in Example 2, except that the pre-lithiation process in step (4) was as follows: 1 g of few-layer phosphorene powder and 0.3 g of lithium powder were added to a glass bottle in a glove box and mixed evenly, and the mixture was kept at 100 °C for 24 h to obtain the pre-lithiated phosphorene material.
[0106] The first reversible specific capacity of the pre-lithiated phosphorene material prepared in this comparative example 3 is 1423 mA h g-1 , the capacity retention rate after 50 cycles is 31.2%.
[0107] Figure 1 This is a SEM image of the pre-lithiated phosphorene material prepared in Example 2 of the present invention. Figure 1 It can be seen that the product morphology is a two-dimensional layered structure, indicating that the present invention has successfully prepared a two-dimensional pre-lithiated phosphorene material.
[0108] Figure 2 This is the XPS graph of the pre-lithiated phosphorene material prepared in Example 2 of the present invention. The peak at around 55.5 eV corresponds to Li + , the peak at around 133 eV corresponds to P, indicating that the phosphorene material has been successfully pre-lithiated.
[0109] Figure 3 Electrochemical impedance diagrams of lithium-ion batteries assembled by Example 2, Example 8, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. As can be seen from the figure, relative to the non-pre-lithiated phosphorene material of Comparative Example 1, the negative electrode prepared by the pre-lithiated phosphorene material in Example 2 has a smaller electrochemical impedance, indicating that pre-lithiation of the phosphorene material is more conducive to improving the performance of the lithium-ion battery. Compared with the pre-lithiated phosphorene material of Comparative Example 2, the electrochemical impedance of the pre-lithiated phosphorene material prepared in Example 2 of the present invention is smaller, indicating that compared with pre-lithiation by the calcination method, the pre-lithiated phosphorene material obtained by pre-lithiation by the solution method of the present invention has better electrochemical performance. This is because the solution method can achieve uniform pre-lithiation at the atomic scale, thereby improving the uniformity of lithium on the negative electrode and improving the electrochemical performance of the lithium-ion battery. The electrochemical impedance of the pre-lithiated phosphorene material of Comparative Example 3 is the highest, even higher than that of the non-pre-lithiated phosphorene material of Comparative Example 1. This is because when lithium powder is used as a lithium source for pre-lithiation by calcination, the lithium powder is severely agglomerated, which not only fails to play a role in pre-lithiation, but also has a negative impact on the overall performance of the phosphorene material. This shows that whether lithium powder is used as a lithium source or lithium foil is used as a lithium source, the electrochemical properties of the phosphorene material obtained by pre-lithiation by calcination are not ideal, and are lower than the pre-lithiated phosphorene material obtained by pre-lithiation by solution method in the present invention, which also shows that the pre-lithiation by solution method in the present invention is a more effective method.
[0110] Compared with the pre-lithiated phosphorene material prepared in Example 8, the electrochemical impedance of the pre-lithiated phosphorene material prepared in Example 2 is smaller, indicating that the pre-lithiated phosphorene material obtained by using bulk black phosphorus as a phosphorus source has better electrochemical performance.
[0111] Figure 4The cycle-specific capacity diagram of the lithium-ion battery assembled by Example 2, Example 8, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. It can be seen from the figure that, relative to the non-pre-lithiated phosphorene material of Comparative Example 1, the pre-lithiated phosphorene material in Example 2 has higher specific capacity and cycle stability. It can also be seen from the figure that compared with the pre-lithiated phosphorene material of Comparative Example 2, the pre-lithiated phosphorene material prepared in Example 2 of the present invention has a higher specific capacity, indicating that compared with the pre-lithiated phosphorene material of Comparative Example 2, the pre-lithiated phosphorene material prepared by the solution method can obtain a pre-lithiated phosphorene material with better electrochemical performance than the pre-lithiated material by the calcination method, which is consistent with the above-mentioned electrochemical impedance results. At the same time, the pre-lithiated phosphorene material of Comparative Example 3 has the lowest specific capacity. This is because the lithium powder agglomerates during the calcination process, and uniform pre-lithiation cannot be achieved, and the overall performance of the phosphorene material is adversely affected, which is consistent with the above-mentioned electrochemical impedance results.
[0112] Figure 5 The cycle-efficiency diagram of the lithium-ion batteries assembled by Example 2, Example 8, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention. It can be seen that, relative to the non-pre-lithiated phosphorene material of Comparative Example 1, the pre-lithiated phosphorene material in Example 2 has a higher and more stable cycle efficiency, which also shows that the lithium-ion battery assembled in Example 2 has a more stable negative electrode-electrolyte interface, reduces the occurrence of side reactions, and improves the cycle stability. In addition, the cycle efficiency of the pre-lithiated phosphorene material in Example 2 is higher than that of the pre-lithiated phosphorene materials in Comparative Examples 2 and 3. This is because Example 2 of the present invention adopts a solution method for pre-lithiation, which makes the distribution of lithium elements in the phosphorene material more uniform, while improving the efficiency of the lithium-ion battery, improving the structural stability of the negative electrode, and improving the cycle performance of the lithium-ion battery.
[0113] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A method for preparing a pre-lithiated phosphorene material, characterized in that: include: The lithium salt and phosphorene are added to the first solvent, ultrasonicated, and then centrifuged. The obtained supernatant is filtered and the obtained filter cake is dried to obtain the pre-lithiated phosphorene material.
2. The method for preparing the pre-lithiated phosphorene material according to claim 1, characterized in that: The lithium salt is one or more of LiNO3, LiClO4, LiBF4, LiPF6, LiBOB, LiPO2F2, LiF, Li2CO3, CF3CO2Li and Li2O.
3. The method for preparing the pre-lithiated phosphorene material according to claim 1, characterized in that: The preparation method of phosphorene is: ball milling a phosphorus material to obtain exfoliated phosphorene; wherein the phosphorus material is one or more of red phosphorus powder, black phosphorus powder and block black phosphorus.
4. The method for preparing the pre-lithiated phosphorene material according to claim 1, characterized in that: The first solvent is one or more of N-methylpyrrolidone, N,N-dimethylformamide, ethanol, ethylene glycol, acetonitrile and acetone.
5. The method for preparing the pre-lithiated phosphorene material according to claim 1, characterized in that: The mass ratio of lithium salt and phosphorene is (0.1~0.5):
1.
6. The method for preparing the pre-lithiated phosphorene material according to claim 1, characterized in that: The ultrasound time is 0.5~5h.
7. The pre-lithiated phosphorene material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The invention comprises phosphorene and lithium element, wherein the lithium element and phosphorene form a Li-P bond.
8. A negative electrode, characterized in that It comprises a current collector and a negative electrode material loaded on the current collector, wherein the negative electrode material is the pre-lithiation phosphorene material according to claim 7.
9. The method for preparing the negative electrode according to claim 8, characterized in that: include: The pre-lithiated phosphorene material, the conductive agent and the binder are mixed, added into a second solvent, and stirred to obtain a slurry; the slurry is coated on a current collector, and dried to obtain a negative electrode.
10. A lithium ion battery, characterized in that: Comprising the negative electrode as claimed in claim 8.
Citation Information
Patent Citations
A method for preparing lithium strips by continuous electrodeposition
CN106702441B
Method for preparing pre-lithiation agent through electrochemical process
CN112542581A
A method for preparing a pre-lithiated lithium-ion battery with a negative electrode and the pre-lithiated lithium-ion battery with a negative electrode
CN112786971B
Method for preparing phosphaalkene by utilizing electrochemistry
CN104779380A
Black phosphorus / reduced graphene oxide composite electrode, preparation method thereof, and flexible lithium ion battery including the composite electrode
CN110391398A